Conjugated Porous Polymers Based on BODIPY and BOPHY Dyes in Hybrid Heterojunctions for Artificial Photosynthesis. (27th August 2021) - Collado, Laura; Naranjo, Teresa; Gomez‐Mendoza, Miguel; López‐Calixto, Carmen G.; Oropeza, Freddy E.; Liras, Marta; Marugán, Javier; de la Peña O'Shea, Víctor A.
Abstract: Developing highly efficient photocatalysts for artificial photosynthesis is one of the grand challenges in solar energy conversion. Among advanced photoactive materials, conjugated porous polymers (CPPs) possess a powerful combination of high surface areas, intrinsic porosity, cross‐linked nature, and fully π‐conjugated electronic systems. Here, based on these fascinating properties, organic–inorganic hybrid heterostructures composed of CPPs and TiO2 for the photocatalytic CO2 reduction and H2 evolution from water are developed. The study is focused on CPPs based on the boron dipyrromethene (BODIPY) and boron pyrrol hydrazine (BOPHY) families of compounds. It is shown that hybrid photocatalysts are active for the conversion of CO2 mainly into CH4 and CO, with CH4 production 4 times over the benchmark TiO2 . Hydrogen evolution from water surpassed by 37.9‐times that of TiO2, reaching 200 mmol gcat −1 and photonic efficiency of 20.4% in the presence of Pt co‐catalyst (1 wt% Pt). Advanced photophysical studies, based on time‐resolved photoluminescence and transient absorption spectroscopy, reveal the creation of a type II heterojunction in the hybrids. The unique interfacial interaction between CPPs and TiO2 results in longer carriers' lifetimes and a higher driving force for electron transfer, opening the door to a new generation of photocatalysts for artificial photosynthesis. Abstract : Artificial photosynthesis is a challenging energy solution for the conversion of sunlight into solar fuels. Hybrid heterostructures, composed of conjugated porous polymers and TiO2, show remarkable photoactivity toward CO2 photoreduction and H2 evolution from water. Photophysical studies reveal the creation of a type II heterojunction that leads to longer carrier lifetimes and a higher driving force for electron transfer in artificial photosynthesis.